ANALISIS PENGGUNAAN LAGU “KALAU KAU SUKA HATI” DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI DI TK AL- IKHTIAR RIANDO - teti, Teti Dwi Jayanti; Ahmadin; Abdussahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language ability in early childhood serves as an essential foundation for communication development. However, in learning practices, several obstacles are still encountered, such as children’s limited vocabulary mastery and the lack of variety in teaching methods. This study aims to examine the use of the song “Kalau Kau Suka Hati” in improving the language skills of early childhood learners at TK Al-Ikhtiar Riando. This research employed a qualitative approach with a case study method. The research subjects consisted of 15 Group B children aged 5–6 years, while the informants included teachers, parents, and children. Data were collected through participatory observation, in-depth interviews, and documentation, and were then analyzed using an interactive analysis model. The findings indicate that the use of the song “Kalau Kau Suka Hati” was implemented through three stages: song exploration, reinforcement through movement, and language creativity development. The improvement in children’s language skills was reflected in the development of active vocabulary mastery, which initially ranged from 600–900 words and became more varied; increased speaking fluency; better understanding of sentence structures using the “if... then...” pattern; and greater confidence in self-expression. The song, which features repetitive lyrics, a cheerful melody, and concrete movements, proved effective in creating engaging and enjoyable multisensory learning. Therefore, “Kalau Kau Suka Hati” can be used as an effective learning medium to support the development of language skills in early childhood.